Effects of an intergenerational Kindermusik class on stress and affect in older adults with dementia and their caregivers: a pilot study using ecological momentary assessment - Thro, Amber; Babcock, Phyllis; Covington, T. Lee; Green, Kelly; Penney, Carol; Fanning, Jason; Hugenschmidt, Christina E. (Frontiers in Aging, 2025)
IntroductionThe objectives of this pilot study were to determine the feasibility of collecting ecological momentary assessments from caregivers of older adult persons with dementia as they attended a weekly, intergenerational Kindermusik class, and to examine relationships between Kindermusik participation and momentary stress and affect for the caregiver and person with dementia.MethodsOver a 12-week period, 14 persons with dementia attended a weekly intergenerational Kindermusik class. Caregivers completed up to six daily ecological momentary assessments on affective valence and stress for themselves and the person with dementia during Weeks 1 and 12. Salivary cortisol data were collected from the persons with dementia during Weeks 1 and 12.ResultsOverall, ecological momentary assessment response rates were low (37.7% completion). Caregiver ecological momentary assessment ratings of their personal stress and affect were significantly and positively associated with their perceptions of affect and stress in the person with dementia. The caregiver’s affective state tended to improve on days when the person with dementia attended Kindermusik, especially when they perceived the person with dementia as having more positive affect.DiscussionAdditional research is required to determine how to best support survey completion while minimizing caregiver burden, and to investigate the impact of more frequent involvement in an intergenerational music and movement program.